Do Socioeconomic Disparities Exist in Postoperative Opioid Prescription and Consumption?. Issue 12 (December 2020) - Srinivasan, Maya Lakshmi; Zaveri, Shruti; Nobel, Tamar; Khetan, Prerna; Divino, Celia M.
Background: Since 1999, >200 000 people in the United States have died from a prescription opioid overdose. Lower socioeconomic status (SES) is one important risk factor. This study investigates socioeconomic disparities in postoperative opioid prescription and consumption. Methods: September 2018-April 2019, 128 patients were surveyed postoperatively regarding opioid consumption. The neighborhood disadvantage was calculated using area deprivation index (ADI). The top 3 quartiles were "high SES" and the bottom quartile "low SES." Results: The study population included 96 high SES patients, median ADI 6 (2-12.3) and 32 low SES, median ADI 94.5 (81.3-97.3). For both, median Oxycodone 5 mg prescribed was 20 pills. 29.2% of high SES consumed 0 pills, 40.6% consumed 1-9 pills, and 27.1% consumed 10+ pills. 25.0% of low SES consumed 0 pills, 46.9% consumed 1-9 pills, and 18.8% consumed 10+ pills. No significant difference in opioid prescription ( P = .792) or consumption ( P = .508) between SES groups. Discussion: Patients of all SES are prescribed and consumed opioids in similar patterns with no significant difference in postoperative pain following ambulatory surgery.